The Relationship between Worm Infection and Stunting in Children in Central Lombok Regency, West Nusa Tenggara Province - Ananta Fittonia Benvenuto; I Gede Angga Adnyana; Velia Maya Samodra; Fahriana Azmi (Universitas Aisyah Pringsewu, 2022)
Stunting is a condition of weight that is not in accordance with the height for children his age, caused by internal factors, namely low nutrition, inadequate maternal nutritional intake during pregnancy and external factors, namely pregnancy infection in the mother and the presence of infectious diseases in children. Worm infection is one of the most common diseases in children. This study aims to determine the relationship between intestinal worm infection and the incidence of stunting in children and the risk factors associated with intestinal worm infection in Central Lombok district, NTB province. A cross-sectional survey was conducted on 170 children with stunting in Central Lombok Regency, West Nusa Tenggara Province. This research took place from January-March 2021. The sample of this study was children with stunting in 8 Puskesmas in Central Lombok Regency. This study used a purposive sampling method, the independent variable was intestinal worm infection and the dependent variable was stunting. The children's parents were given an informed consent form, a set of personal protective equipment in the form of a mask and a pair of handscones, a stool pot, plastic, and oil paper. Children were also taken blood for ELISA examination, the primary data obtained in this study. Data analysis with SPSS is univariate test. There were 19 (11.17%) of the total 170 subjects infected with intestinal worms in Central Lombok Regency with a mean age of 32.64±13.75. Intestinal worm species include Ascaris lumbricoides 18 (10.59%) and Trichuris trichiura 1 (0.58%). There was no significant risk factor between intestinal helminth infection and stunting in children (95% CI = 33.47-49.36, with p value = 0.695) on blood examination using the ELISA method for levels of IL-4 as a marker of intestinal worm infection and on stool examination by the Lugol method in children in Central Lombok Regency. However, there was a significant relationship between anemia and intestinal worm infection in stunted children (p = 0.029). There is a relationship between intestinal worm infection and stunting in children in Central Lombok Regency, NTB Province. Anemia is a risk factor associated with the incidence of intestinal worm infection. However, the small number of samples and the short time in this study showed insignificant results between the two variables.